2020
DOI: 10.1155/2020/2363545
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Predicting Recurrence-Free Survival in Chinese Women with Endometrial Cancer after Initial Therapy: External Validation

Abstract: This study aimed at developing an available recurrence-free survival (RFS) model of endometrial cancer (EC) for accurate and individualized prognosis assessment. A training cohort of 520 women with EC who underwent initial surgical treatment and an external validation cohort of 445 eligible EC patients from 2006 to 2016 were analyzed retrospectively. Multivariable Cox proportional hazards regression models were used to develop nomograms for predicting recurrence. The concordance index (C-index) and the area un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Those aged over 80 years had a high risk and a shorter OS (50–59 years: hazard ratio [HR] 1.93, 95% confidence interval [CI] 1.61–2.32; ≥80 years: HR 8.39, 95% CI 6.98–10.07). This finding was consistent with the results of other studies, 8,10,11 except for Bendifallah et al, 9 who indicated by a nomogram that the level of evidence for an association with OS for age was inconclusive. Research by Kang et al 12 showed that para‐aortic lymph node metastasis was not associated with age.…”
Section: Discussionsupporting
confidence: 92%
“…Those aged over 80 years had a high risk and a shorter OS (50–59 years: hazard ratio [HR] 1.93, 95% confidence interval [CI] 1.61–2.32; ≥80 years: HR 8.39, 95% CI 6.98–10.07). This finding was consistent with the results of other studies, 8,10,11 except for Bendifallah et al, 9 who indicated by a nomogram that the level of evidence for an association with OS for age was inconclusive. Research by Kang et al 12 showed that para‐aortic lymph node metastasis was not associated with age.…”
Section: Discussionsupporting
confidence: 92%
“…Of these 65 studies, 27 papers met the criteria for meta-analysis, which included an overall number of 75897 patients. Of the 27 papers, 16 studies (11,13,21,22,24,35,36,43,49,54,58,62,68,70,73,77) included OS data, 18 had DFS data(14,21,62,64,68,70,72,74,77,78,25,36,39,43,44,49,53,58), and 7 had CSS(7)(19)(33)(44)(45)(64)(73). The quality assessment (QUIPS) of included studies is summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, FIGO staging system has limitations in accurately predicting the prognosis of EC patients. Especially, it cannot explain why patients with the same stage and grade have different clinical outcomes [ 17 ]. The reason may be that ignoring the influence of other prognostic factors.…”
Section: Discussionmentioning
confidence: 99%